2016
DOI: 10.1063/1.4944492
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional infrared spectroscopy of vibrational polaritons of molecules in an optical cavity

Abstract: Strong coupling of molecular vibrations to an infrared cavity mode affects their nature by creating dressed polariton states. We show how the single and double vibrational polariton manifolds may be controlled by varying the cavity coupling strength, and probed by a time domain 2DIR technique, Double Quantum Coherence (DQC).Applications are made to the amide-I (CO) and amide-II (CN ) bond vibrations of N − methylacetamide (NMA).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 47 publications
2
60
0
Order By: Relevance
“…Another nonrephasing pathway that is usually difficult to measure is the so-called double-quantum version of 2D IR spectroscopy that is emitted in the k 1 + k 2 − k 3 direction. There has been past 44 and recent 45 interest in this particular implementation of 2D IR due to the ease of measuring vibrational couplings and anharmonicities. This pathway is not usually measured because it further complicates the most common experimental geometries.…”
Section: The 2d Ir Experimentsmentioning
confidence: 99%
“…Another nonrephasing pathway that is usually difficult to measure is the so-called double-quantum version of 2D IR spectroscopy that is emitted in the k 1 + k 2 − k 3 direction. There has been past 44 and recent 45 interest in this particular implementation of 2D IR due to the ease of measuring vibrational couplings and anharmonicities. This pathway is not usually measured because it further complicates the most common experimental geometries.…”
Section: The 2d Ir Experimentsmentioning
confidence: 99%
“…In parallel, groups pursue the investigation of the influence of the coupling between the different degrees of freedom in polaritonic systems. It is important to consider the vibronic structure to model fluorescence, while the effects of anharmonicity of the vibrational modes are also investigated under the strong coupling regime. The study of the interaction between photons, excitons, and vibrations is useful for understanding luminescence and light‐harvesting complexes .…”
Section: Quantum Mechanical Aspects Of Strong Couplingmentioning
confidence: 99%
“…The quantum coherence of polaritons gives opportunities to control transport properties of materials. For instance, the study of the energy transfers inside matter under the strong coupling regime by 2D infrared spectroscopy for the amide‐I (CO) and amide‐II (CN) vibrations demonstrated that the coupling influences directly the vibrational excitation lifetimes. The vibration lifetimes are also strongly modified in this pump–probe infrared absorption study of the CO group stretching vibration, with additional evidence of coherent energy transfers between the two polaritons provided by the prediction of quantum beats.…”
Section: Strong Coupling Applicationsmentioning
confidence: 99%
“…12 Its potential application to molecular cooling, 13,14 as a tool to probe larger molecules, 15,16 to enhance vibrational spectra, [17][18][19][20] for use with electromagnetically induced transparency, 21 and to expedite cavity-modified photo chemistry 22,23 have been objects of intensive studies. Strong cavity coupling in molecular systems has been demonstrated recently for electronic transitions 24 and for vibrational transitions.…”
mentioning
confidence: 99%